(untitled) (Revista científica Olimpia, 2021)
The current research offers a general view for the initiation in swimming of schoolchildren with motor disabilities. This analysis is offered with an emphasis on the Familiarization stage, in which the competition regulations established for this disability in Paralympic swimming are expressed together with the guidelines stated the Athlete Preparation Program for swimming. Considering the above-mentioned elements, the above exercises are adapted and methodological indications are offered for this stage. All these elements provide coaches with tools which will facilitate the training process with higher quality in the completion of the objectives, and in a higher number of prepared athletes that will eventually be part of the pyramid of sports performance of swimming.